The Multilevel Cycle of Anthropogenic Zinc - T. E. Graedel; Dick van Beers; Marlen Bertram; Kensuke Fuse; Robert B. Gordon; Alexander Gritsinin; Ermelinda M. Harper; Amit Kapur; Robert J. Klee; Reid Lifset; Laiq Memon; Sabrina Spatari (Journal of Industrial Ecology, 2005)
Summary A comprehensive annual cycle for stocks and flows of zinc, based on data from circa 1994 and incorporating information on extraction, processing, fabrication, use, discard, recycling, and landfilling, was carried out at three discrete governmental unit levels—54 countries and 1 country group (which together comprise essentially all global anthropogenic zinc stocks and flows), nine world regions, and the planet as a whole. All of these cycles are available in an electronic supplement to this article, which thus provides a metadata set on zinc flows for the use of industrial ecology researchers. A “best estimate” global zinc cycle was constructed to resolve aggregation discrepancies. Among the most interesting results are the following: (1) The accumulation ratio, that is, addition to in‐use stock as a function of zinc entering use, is positive and large (2/3 of zinc entering use is added to stock) (country, regional, and global levels); (2) secondary input ratios (fractions of input to fabrication that are from recycled zinc) and domestic recycling percentages (fractions of discarded zinc that are recycled) differ among regions by as much as a factor of six (regional level); (3) worldwide, about 40% of the zinc that was discarded in various forms was recovered and reused or recycled (global level); (4) zinc cycles can usefully be characterized by a set of ratios, including, notably, the utilization efficiency (the ratio of manufacturing waste to manufacturing output: 0.090) and the prompt scrap ratio (new scrap as a fraction of manufacturing input: 0.070) (global level). Because capturable discards are a significant fraction of primary zinc inputs, if a larger proportion of discards were recaptured, extraction requirements would decrease significantly (global level). The results provide a framework for complementary studies in resource stocks, industrial resource utilization, energy consumption, waste management, industrial economics, and environmental impacts.